2005
DOI: 10.1017/s0305000905006963
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child picture-book reading, mothers' mental state language and children's theory of mind

Abstract: This study focuses on parent–child book reading and its connection to the development of a theory of mind. First, parents were asked to report about frequency of parent–child storybook reading at home. Second, mothers were asked to read four picture-books to thirty-four children between 4;0 and 5;0. Both frequency of parent–child storybook reading at home, and mother's use of mental state terms in picture-books reading tasks were significantly associated with success on false belief tasks, after partialling ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 19 publications
(34 reference statements)
12
135
2
4
Order By: Relevance
“…Therefore, emotion language is not just a component of emotional competence; it is also a manifestation of 'theory of mind ' (ToM), the child's growing awareness of the existence of internal states in itself and in others (Harris, 1989 ;. Both cross-sectional (Dunn, Brown & Beardsale, 1991 ;Astington & Jenkins, 1999 ;de Villiers & de Villiers, 2000 ;Adriàn, Clemente, Villanueva & Rieffe, 2005;Astington & Baird, 2005) and training (Lohmann & Tomasello, 2003 ;Hale & Tager-Flusberg, 2003 ;Grazzani Gavazzi & Ornaghi, 2008) studies have shown that language plays a crucial role in fostering children's understanding of the mind (Milligan, Astington & Dack, 2007). Recent findings support the hypothesis of a bi-directional relationship between theory of mind and language (Slade & Ruffman, 2005) although the effect of language on theory of mind seems to be stronger than the other way round.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, emotion language is not just a component of emotional competence; it is also a manifestation of 'theory of mind ' (ToM), the child's growing awareness of the existence of internal states in itself and in others (Harris, 1989 ;. Both cross-sectional (Dunn, Brown & Beardsale, 1991 ;Astington & Jenkins, 1999 ;de Villiers & de Villiers, 2000 ;Adriàn, Clemente, Villanueva & Rieffe, 2005;Astington & Baird, 2005) and training (Lohmann & Tomasello, 2003 ;Hale & Tager-Flusberg, 2003 ;Grazzani Gavazzi & Ornaghi, 2008) studies have shown that language plays a crucial role in fostering children's understanding of the mind (Milligan, Astington & Dack, 2007). Recent findings support the hypothesis of a bi-directional relationship between theory of mind and language (Slade & Ruffman, 2005) although the effect of language on theory of mind seems to be stronger than the other way round.…”
Section: Introductionmentioning
confidence: 91%
“…For example, during unstructured play sessions mother's tendency to comment on emotions and desires (e.g., happy, sad, hate, love, hurt, sorry) that were appropriate to the situation predicted children's theory of mind [64]. Comparable results were found between a child's theory of mind and their parent's tendency to talk about mental states (e.g., intentions, beliefs) when reading with their child [65,66,61]. Similarly, parent-guided reminiscing about past events allowed children to construct relations between both the past and present, as well as the self and other, which is critical to the development of theory of mind [67].…”
Section: The Role Of Parents In the Development Of Social Perspectivementioning
confidence: 96%
“…In children, use of terms for mental states (desires, emotions, etc.) as well as success in theory-of-mind tasks was studied by Adrian et al (2005). Children's use of terms for mental states and their abilities in theory of mind were found to be related both to the amount of reading mothers did with them and to the number of mental state terms that mothers used when they read picture books to their children.…”
Section: Effects Of Literaturementioning
confidence: 99%